2012
DOI: 10.1371/journal.pone.0043924
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Microglia Activation in the Lead Induced Long-Term Potentiation Impairment

Abstract: Exposure of Lead (Pb), a known neurotoxicant, can impair spatial learning and memory probably via impairing the hippocampal long-term potentiation (LTP) as well as hippocampal neuronal injury. Activation of hippocampal microglia also impairs spatial learning and memory. Thus, we raised the hypothesis that activation of microglia is involved in the Pb exposure induced hippocampal LTP impairment and neuronal injury. To test this hypothesis and clarify its underlying mechanisms, we investigated the Pb-exposure on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 36 publications
3
64
1
Order By: Relevance
“…Multitargets could be involved. In our previous study, we found that Pb exposure caused LTP impairment through the release of cytokine by the activated microglia [21]. In this study, we found that AMPA receptor phosphorylation and NR2A downregulation could possibly contribute to LTP impairment and development of dendritic spine change, which could be the cause of the behavior change of Pb-treated rats.…”
Section: Multitargets Of Pb Exposure On Ltp Impairment and Behavior Cmentioning
confidence: 57%
“…Multitargets could be involved. In our previous study, we found that Pb exposure caused LTP impairment through the release of cytokine by the activated microglia [21]. In this study, we found that AMPA receptor phosphorylation and NR2A downregulation could possibly contribute to LTP impairment and development of dendritic spine change, which could be the cause of the behavior change of Pb-treated rats.…”
Section: Multitargets Of Pb Exposure On Ltp Impairment and Behavior Cmentioning
confidence: 57%
“…For instance, incubation of lead at the concentrations of 0.25–1.0 μM (5.2–20.7 μg/dL) for 7–21 days resulted in an obvious reduction in functions of primary cultures of rat astrocytes (Lidsky and Schneider, 2003). Our published studies showed that short-term treatment of lead (within 48 h) at 50 μM (1035.2 μg/dL) activated the primary cultured rat microglia (Liu et al, 2012). To further reveal the molecular basis for lead activation of microglia, we used acute lead exposure here since COX-2 is an immediate early response gene, and during our observance periods (within 24 h), no severe cell death was observed.…”
Section: Discussionmentioning
confidence: 99%
“…1 One of the heavy metals, lead has threatened environment sustainability and our future generations. Although research on lead neurotoxicity has been of interest for many years, [2][3][4][5][6][7] the effects of lead on the expression of MMP2 and MMP9 in the cerebral cortex and hippocampus still need to be elucidated.…”
Section: Introductionmentioning
confidence: 99%